Research on key technologies of safety monitoring data sharing for railway engineering construction based on blockchain - Yuhong LIU; Liang YANG; Chunhui PIAO; Zhiguo ZHANG (Tongxin xuebao)
In order to solve the problems that the monitoring data was easy to be tampered with in the process of railway engineering construction safety monitoring, and the authenticity of the data might be questioned during the accountability of accidents, a blockchain-based railway engineering construction safety monitoring data sharing model was proposed.The characteristics of automatic execution of smart contracts ensured the transparency of the process of monitoring data on the chain.In the PBFT algorithm, there was a problem that the Byzantine nodes and the normal nodes were selected as the master node with the same probability, a reputation-based practical Byzantine fault tolerance algorithm was proposed.Streaming data on the chain might cause network congestion, which simplified the consensus protocol and reduced the time complexity from O(n2) to O(n).A comparative experiment was conducted using Hyperledger Caliper to prove that the delay of the improved algorithm is lower than PBFT algorithm, and the throughput is higher than PBFT algorithm.A quantitative analysis of the possibility of attack and the probability of successful attack was carried out, and it was determined that the smart contract provides tamper-proof modification for the monitoring data on the chain.Comparative analysis proves that the proposed blockchain-based railway engineering construction safety monitoring data sharing model is good than other models in terms of consensus efficiency, TPS and block generation speed.